Feeding problems in children with autism spectrum disorders: a systematic review - Pinto Silva, Rita (2022)
Feeding problems are often associated with Autism Spectrum Disorders. However, many terms are used to describe these problems with a lack of consensus between authors. This systematic review critically examines the available scientific literature on the most commonly described characteristics of feeding disorders among children with Autism Spectrum Disorders. The literature was evaluated according to PRISMA standards by searching electronic databases (e.g., MEDLINE, EBSCO) with reference lists from January 2009 to January 2019. English language studies were included. Abstract and full-text article reviews were conducted by two independent authors with sequential data extraction. The systematic search and the subsequent analysis of the results revealed 45 articles eligible for full review. Detailed information regarding the methods and results was extracted from the original articles, and the quality of the included studies was appraised. The most commonly described feeding problem was food selectivity followed by mealtime behaviour problems. We also found some frequently associated issues like sensory sensitivity as well as anthropometric deviations and nutritional deficits that can negatively impact health. Oral motor impairment was a less commonly studied phenomenon. Most of the reviewed studies were considered to have a ‘moderate’ level of evidence. Although current evidence suggests that feeding problems are often associated with autism, more research is needed to understand the reliability and validity between and within existing feeding definitions and measures, as well as into the prevalence of oral sensory-motor related deficits.